2018
DOI: 10.1101/446161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glass confers rhabdomeric photoreceptor identity inDrosophila, but not across all metazoans

Abstract: Across metazoans, visual systems employ different types of photoreceptor neurons to detect light. These include rhabdomeric PRs, which exist in distantly related phyla and possess an evolutionarily conserved phototransduction cascade. While the development of rhabdomeric PRs has been thoroughly studied in the fruit fly Drosophila melanogaster, we still know very little about how they form in other species. To investigate this question, we tested whether the transcription factor Glass, which is crucial for inst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…As we have described, our results have demonstrated that PIP82 is regulated by a conserved set of transcription factors for rhabdomeric photoreceptor differentiation in insects, found in both open or fused rhabdom configurations [ 19 , 21 , 65 ]. Our data demonstrated the key regulator is the zinc finger protein Glass and a feed forward loop that requires the photoreceptor specific transcription homeodomain transcription factor Pph13 for maximum expression [ 30 ].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…As we have described, our results have demonstrated that PIP82 is regulated by a conserved set of transcription factors for rhabdomeric photoreceptor differentiation in insects, found in both open or fused rhabdom configurations [ 19 , 21 , 65 ]. Our data demonstrated the key regulator is the zinc finger protein Glass and a feed forward loop that requires the photoreceptor specific transcription homeodomain transcription factor Pph13 for maximum expression [ 30 ].…”
Section: Discussionmentioning
confidence: 78%
“…Subsequently, we identified PIP82 in two different transcriptome studies designed to identify genes required for the differentiation of Drosophila photoreceptors [ 24 , 25 ]. In particular, our transcriptome analyses suggested that PIP82 is part of the Glass-Pph13 dependent transcriptional cascade that is essential for photoreceptor cell development [ 19 , 25 , 26 ]. Recent studies revealed that Glass has two temporal roles with respect to retina development, specification and differentiation [ 19 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations